Effects of ingesting protein in combination with carbohydrate during exercise on endurance performance: A systematic review with meta-analysis - Stearns, R. L.; Emmanuel, H.; Volek, J. S.; Casa, D. J. (The Journal of Strength and Conditioning Research, 2010)
Coingestion of protein with carbohydrate has been shown to enhance muscle recovery, particularly after intense bouts of exercise. However, performance benefits of ingesting a protein-carbohydrate drink during exercise remains unclear. Therefore, we used a systematic review with meta-analysis to examine the influence of protein ingestion during exercise on subsequent endurance performance. Eleven qualifying studies were included that contained 3 time-trial and 8 time-to-exhaustion cycling protocols. Only 3 of these studies controlled for caloric content and contained an isocaloric trial. Of the 11, 4 reported significant differences between a control and protein trial; however, none of these were isocaloric studies. The 3 time-trial protocols showed no significant improvement with protein. The meta-analysis of the time-trial studies revealed no significant overall effect (p = 0.73), whereas meta-analysis of time-to-exhaustion studies revealed a significant effect (p = 0.008). Of the time-to-exhaustion trials, the isocaloric studies found no significant effect (p = 0.71), whereas the isocarbohydrate studies revealed a significant effect (p = 0.05). The average percent improvement with ingestion of protein was 9.0%. The isocarbohydrate studies reported an improvement of 10.5%, whereas the isocaloric studies revealed a 3.4% improvement. We conclude that compared to carbohydrate alone, coingestion of protein and carbohydrate during exercise demonstrated an ergogenic effect on endurance performance when assessed by time to exhaustion and also where supplements were matched for carbohydrate (isocarbohydrate). Thus, the ergogenic effect of protein seen in isocarbohydrate studies may be because of a generic effect of adding calories (fuel) as opposed to a unique benefit of protein. Further research is warranted before a clear conclusion can be drawn.